2018
DOI: 10.1021/acs.jmedchem.7b01895
|View full text |Cite
|
Sign up to set email alerts
|

Dual Nicotinic Acetylcholine Receptor α4β2 Antagonists/α7 Agonists: Synthesis, Docking Studies, and Pharmacological Evaluation of Tetrahydroisoquinolines and Tetrahydroisoquinolinium Salts

Abstract: We describe the synthesis of tetrahydroisoquinolines and tetrahydroisoquinolinium salts together with their pharmacological properties at various nicotinic acetylcholine receptors. In general, the compounds were α4β2 nAChR antagonists, with the tetrahydroisoquinolinium salts being more potent than the parent tetrahydroisoquinoline derivatives. The most potent α4β2 antagonist, 6c, exhibited submicromolar binding K and functional IC values and high selectivity for this receptor over the α4β4 and α3β4 nAChRs. Whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 49 publications
1
9
0
Order By: Relevance
“…For the contacts indicated by the two best models ( Table 2 ), there is an agreement regarding the contact between the carbon atom of residue A:W156, reinforcing its importance. Such contact represents a hydrogen bond between the hydrogen atom bound to the basic nitrogen atom of the ligand and the carbonyl group located in the A:W156 residue, in agreement with several research groups that reported the importance of this interaction for molecular recognition of ligands targeting the α4β2 nAChRs [ 20 , 21 , 22 , 23 ]. The contact of the CG atom located in residue A:Y204 ( Figure 2 a) in the model nAChRs_α4β2_1 represents hydrophobic interactions as a result of the A:W156 hydrogen bond, as it tends to orient the α-N carbon atoms towards this residue.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…For the contacts indicated by the two best models ( Table 2 ), there is an agreement regarding the contact between the carbon atom of residue A:W156, reinforcing its importance. Such contact represents a hydrogen bond between the hydrogen atom bound to the basic nitrogen atom of the ligand and the carbonyl group located in the A:W156 residue, in agreement with several research groups that reported the importance of this interaction for molecular recognition of ligands targeting the α4β2 nAChRs [ 20 , 21 , 22 , 23 ]. The contact of the CG atom located in residue A:Y204 ( Figure 2 a) in the model nAChRs_α4β2_1 represents hydrophobic interactions as a result of the A:W156 hydrogen bond, as it tends to orient the α-N carbon atoms towards this residue.…”
Section: Resultssupporting
confidence: 87%
“…The search radius for both models was set as 10 Å, and rigid docking was performed, considering 50 docking poses for each ligand. For the (α4) 2 (β2) 3 model, a molecule of water was modeled in the active site region at coordinates x = 69.3500, y = −22.8900, and z = −42.4450, in accordance with published works [ 20 , 37 ]. Regarding the α7 subtype model, a water molecule was modeled at coordinates x = −17.5010, y = −12.1430, and z = 5.4700, corresponding to the position of a co-crystallized water molecule.…”
Section: Methodsmentioning
confidence: 99%
“…[201] Kristensen's group designed and synthesized a series of tetrahydroisoquinolines and tetrahydroisoquinolinium salts to explore novel nAChR ligands and (R)-enantiomers were proved to be essentially active at 𝛼4𝛽2 subtype. [202] Compound 170 (Figure 25) displayed a highly binding affinity to 𝛼4𝛽2-nAChR (K i = 0.17 × 10 −6 m) and selectivity over 𝛼3𝛽4-nAChR (K i = 100 × 10 −6 m), and compound 171 showed better profile for nAChRs (𝛼4𝛽2-nAChR: K i = 0.045 × 10 −6 m and 𝛼3𝛽4-nAChR: K i = 11 × 10 −6 m). In functional assays, compound 170 was identified as an 𝛼4𝛽2-nAChR antagonist (IC 50 = 1.3 × 10 −6 m) and weak 𝛼7-nAChR agonist, while compound 171 proved to be a potent 𝛼7-nAChR agonist (EC 50 = 1.6 × 10 −6 m) with 𝛼4𝛽2-nAChR antagonism activity (IC 50 = 0.22 × 10 −6 m).…”
Section: Nmdar Positive Allosteric Modulators (Pam)mentioning
confidence: 99%
“…7 (R)-1,2,3,5,6,11b-Hexahydro- [1,3]dioxolo[4,5-g]pyrrolo[2,1-a] isoquinoline ((R)-4) is a potent α4β2 nAChR antagonist and weak α7 agonist. 8 (R)-Harmicine ((R)-5) from the Malaysian plant Kopsia grif fithii has been shown to have antileishmanial activity and antinociceptive properties. 9 (S)-Desbromoarborescidine A ((S)-6) is a plant alkaloid isolated from the New Guinea tree Dracontomelum mangiferum and shows antiproliferative activity.…”
mentioning
confidence: 99%
“…Fused-ring tetrahydroisoquinoline (THIQ) and tetrahydro-β-carboline (THβC) are important motifs in natural products and synthetic biologically active compounds (Figure ), such as valbenazine ( 1 , a selective monoamine transport inhibitor for the treatment of tardive dyskinesia), (+)-arborescidine A (( R )- 2 ) isolated from the marine tunicate Pseudodistoma arborescens with antiproliferative activity, , and ( S )-crispine A (( S )- 3 ) from Carduus crispus L. which has been observed to inhibit the in vitro growth of SKOV3, KB, and HeLa human cancer lines and shows significant cytotoxic activity . ( R )-1,2,3,5,6,11b-Hexahydro-[1,3]­dioxolo­[4,5-g]­pyrrolo­[2,1- a ] isoquinoline (( R )- 4 ) is a potent α4β2 nAChR antagonist and weak α7 agonist . ( R )-Harmicine (( R )- 5 ) from the Malaysian plant Kopsia griffithii has been shown to have antileishmanial activity and antinociceptive properties .…”
mentioning
confidence: 99%